Toward a Legal Standard of Tolerable Heat - Gregor, Ashley M. (Columbia Journal of Environmental Law, 2019)
Heat is the leading cause of weather-related mortality in the United States. Over the past 30 years, extreme heat has claimed, on average, more lives per year than floods and hurricanes combined. The Centers for Disease Control and Prevention reports that extreme heat kills approximately 618 people per year, though, because heat exposure often exacerbates underlying medical conditions, it is likely that many heat-related deaths go misdiagnosed or unrecognized. Despite its significant hazards, the “invisible” threat of extreme heat has gained little traction in the national conversation on climate change, with superstorms and increasingly regular 100-year floods, instead, dominating the media. Recently, however, the dangers of extreme heat—and our lack of preparedness for its impacts—have become far more visible. In September 2017, 14 residents of a Florida nursing home died when Hurricane Irma knocked out power to the building’s air-conditioning system, and indoor temperatures swelled to 99°F. Extreme heat in the summer of 2017 forced airlines to cancel dozens of flights scheduled to depart from Phoenix Sky Harbor International Airport, because, at 118°F, it is too hot for planes to take off safely. In late-October 2017, large swaths of Southern California experienced temperatures near 110°F, the hottest weather ever recorded in the United States so late in the calendar year. The extreme heat in California amplified a devastating season of wildfires—in 2017 alone, 9,000 wildfires ravaged the state, burning 1.2 million acres of land, destroying over 10,800 structures, and killing upwards of 46 people. In November 2018, California experienced its most deadly and destructive wildfire in modern history, when the Camp Fire in Butte County killed at least 84 people and virtually destroyed the town of Paradise, then home to 27,000 people. In Southern California, the Woolsey Fire burned close to 100,000 acres of land in Ventura and Los Angeles Counties. As anthropogenic climate change yields higher temperatures and humidity across the globe, the United States will likely experience a long-term upward trend in heat-related mortality and morbidity. Indeed, in 2016, the Obama administration released a scientific assessment of the impact of climate change on public health, predicting that more than 11,000 additional heat-related deaths may occur during the summer of 2030, with that number increasing to 27,000 additional deaths during the summer of 2100. Moreover, the Intergovernmental Panel on Climate Change (“IPCC”) reports, with virtual certainty, that there will be more frequent daily and seasonal extreme heat events as the 21st century progresses. Climatologists predict that by mid-century, there will be 20 to 30 more days per year with temperatures over 90°F in most areas of the contiguous United States, with the Southeast experiencing increases of 40 to 50 days. By 2100, some areas of Texas may experience more than 100 days over 100°F per year. According to Michael E. Mann, a leading climatologist and professor of meteorology at Pennylvania State University, what we now deem “extreme heat” may soon be called “mid-summer.” As demonstrated by both climate science and recent events, extreme heat is a relevant and significant threat to human health and safety. Currently, however, there is no standardized approach to protecting the populace from extreme heat, let alone a legal standard of tolerable heat applicable to the workplace, housing, or other affected environments. This Note investigates existing laws, regulations, and guidelines on extreme heat in a variety of contexts, and considers the possibility of a quantifiable and uniform standard of acceptable heat. It will analyze proven best practices for tolerating heat and present the most viable small- and large-scale resiliency strategies to prepare for a warming climate. This Note will conclude by acknowledging the limitations of a uniform legal standard of tolerable heat but advocating for adaptive policies based on context and population, with a particular focus on local mitigation techniques.